Exploring MSMEs’ Financial Management Behavior: Financial Literacy, Subjective Norms, and FinTech Payments in Tondano Raya - Jones Xaverius Pontoh; Lihard Stevanus Lumapow (Academic Bright Collaboration, 2026)
Purpose – This study examines the influence of financial literacy, subjective norms, and financial technology (FinTech) payment systems on the financial management behavior of food and beverage MSMEs in Tondano Raya, North Sulawesi, within a behavioral finance framework grounded in the Theory of Reasoned Action. Methods – A quantitative approach was employed using survey data from 35 purposively selected MSME entrepreneurs drawn from a population of 284 business actors. Although the sample size is relatively small for PLS-SEM, the study is positioned as exploratory and the findings should be interpreted cautiously, particularly for non-significant relationships. Findings – The structural model explains 70.5% of the variance in financial management behavior (R² = 0.705). Subjective norms exert a positive and significant effect (β = 0.458, p = 0.004), emerging as the strongest predictor within this exploratory context. Financial literacy shows a positive but non-significant effect (β = 0.433, p = 0.067), suggesting that financial knowledge alone may not automatically translate into financial behavior within this exploratory sample. FinTech payment systems also demonstrate a positive but non-significant effect (β = 0.189, p = 0.387), suggesting that digital payment adoption alone may be insufficient to improve financial management practices unless integrated into organizational routines. Research implications – The findings suggest that policymakers, financial regulators, and MSME support organizations may benefit from supplementing financial education and technology diffusion programs with community-based peer accountability mechanisms and organizational-level digital integration support, as these complementary approaches may prove more effective in improving MSME financial management behavior than standalone capability provision. Originality – Within an exploratory sample of community-oriented MSMEs, this study provides preliminary evidence that social influence may represent a particularly salient contextual factor in shaping financial management behavior alongside cognitive and technological dimensions, while also establishing a theoretically important distinction between FinTech adoption and its organizational routinization as a precondition for behavioral change.